'Observing'' diabetic neuropathy with corneal confocal microscopy: the effect of improvement of risk factors. Issue 6 (November 2011) - Boucek, Petr
Evaluation of: Tavakoli M, Kallinikos P, Iqbal A et al. Corneal confocal microscopy detects improvement in corneal nerve morphology with an improvement in risk factors for diabetic neuropathy. Diabet. Med. 28(10), 1261–1267 (2011). A recent observational study has evaluated whether a novel examination method, corneal confocal microscopy, can be used to detect changes in corneal nerve morphology following improvements of conventional risk factors in diabetic patients with mild-to-moderate neuropathy. At 2-year follow-up, improvement of glycemic control (HbA1c) correlated significantly with increases in corneal nerve fiber density. The results add new supportive evidence to data from previous studies of corneal confocal microscopy for its potential use as a convenient noninvasive technique in trials of therapeutic interventions for diabetic neuropathy. Since so far only intensive glycemic control has been proven as an effective measure, this could represent an important advance in the search for new treatment options for this major diabetic complication.